International investment : theory, analysis, case studies - Mkpakan, Eyo Etim (Lagos : University of Lagos Press, 2004)
The book focuses on foreign direct investment and aspects of portfolio investment. It also highlights some significant problems usually encountered by the developing countries during the process of industrialization. It contains information on international investment transactions between Britain and Nigeria.
Includes bibliographical references and indexes.
oif 15/07/14
Loans
Keywords: Investments, International; Foreign direct investment